Parenting information for parents: Efforts to prepare children to experience menarche in prepubertal young girls - Marianti, Lena; Kushendar, Kushendar; Fitri, Hartika Utami (Universitas Islam Negeri Raden Intan Lampung, 2022)
The role of parents is very important as an effort to provide information to their children, especially young women about the fulfillment of education, especially as women. The purpose of this study was to determine the effectiveness of parenting information to prepare young women for prepubertal menarche. The research method used is a mixed methods model, with a concurrent model design that combines qualitative and quantitative data. This research involved 66 research subjects who were selected purposively from 360 female students at State Junior High School 8 Pagaralam. The research instrument used was the menarche scale and interview guidelines. The collected data were analyzed using multiple regression. The results of the menarche scale analysis and interviews before providing information services about menarche, the percentage of children who are not ready to face menarche is 81% thus there are still children who are afraid, embarrassed, and even anxious about facing menarche. After providing parenting information to parents as an effort to prepare children to experience menarche, prepubertal young women experienced a decrease in the number of children to 18%. Thus parenting information plays a very important role in increasing the knowledge of parents and children about menarche.